2022
DOI: 10.3389/fendo.2022.977105
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival outcomes of pediatric adrenal malignancies: An analysis with the upstaged SEER registry during 2000-2019

Abstract: ObjectiveTo investigate the clinicopathological characteristics and long-term survival outcomes of pediatric adrenal malignancies.MethodThis study retrospectively analyzed children with pathologically confirmed pediatric adrenal malignancies from Surveillance, Epidemiology, and End Results Database from 2000 to 2019. Kaplan-Meier curve was used to assess the overall survival (OS) and cancer-special survival (CSS), and the Log-Rank method was used to calculate statistical differences. Cox proportional hazards m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…We found that patients who received chemotherapy had an adverse prognosis compared with those who did not receive or had an unknown chemotherapy status. Similarly, a SEER-based study of adrenal tumors in children reported a worse prognosis for patients in the chemotherapy group [ 28 ]. Notably, in the SEER database, patients who did not receive chemotherapy and those with unknown chemotherapy were grouped together, which might lead to bias in the results regarding value of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We found that patients who received chemotherapy had an adverse prognosis compared with those who did not receive or had an unknown chemotherapy status. Similarly, a SEER-based study of adrenal tumors in children reported a worse prognosis for patients in the chemotherapy group [ 28 ]. Notably, in the SEER database, patients who did not receive chemotherapy and those with unknown chemotherapy were grouped together, which might lead to bias in the results regarding value of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on the prognosis, diagnosis, and treatment of malignant adrenal tumors. Researchers have found that patient age, the initial stage of diagnosis, and surgical resection might affect the prognosis of patients with adrenal malignancies ( 6 , 21 , 22 ). However, most studies limited the tumor to a single histological type or only studied one prognostic factor and only the OS of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size and stage were probable variables that affected the OS in adrenal tumor patients ( 21 , 29–31 ). Wang et al stated that primary tumor size is a vital prognostic indicator for NB patients, and tumor size >4 cm may anticipate a poor prognosis ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LDH is a catalytic enzyme in the pathways of glycolysis and gluconeogenesis, and exists in most tissues of the body [ 24 , 25 , 26 ]. Cancer cells produce large amount of lactic acid to form an acidic tumor microenvironment, and local high concentration of lactic acid inhibits the function of cytotoxic T lymphocytes and reduces the release of IL‐2, interferon, perforin, and granzyme [ 27 ].…”
Section: Discussionmentioning
confidence: 99%